A review of evidence on mechanical properties of running specific prostheses and their relationship with running performance - Rahnama, Leila; Soulis, Kimberly; Geil, Mark D. (Frontiers in Rehabilitation Sciences, 2024)
BackgroundAlthough mechanical properties of running specific prostheses (RSPs) can affect running performance, manufacturers do not consistently report them. This study aimed to review existing literature on RSP mechanical and structural properties and their relationship with running performance.MethodsA comprehensive search was conducted using keywords related to mechanical properties of RSPs and running performance. Search terms included stiffness and hysteresis, as well as performance outcomes including metabolic cost and running speed. Non-peer-reviewed and non-English publications were excluded.ResultsTwenty articles were included in the review. Sixteen studies used a material testing machine to measure RSP material properties, and four articles used other techniques including 2D/3D video capture and force platforms. Both measurement techniques and reporting of outcomes were inconsistent, which limits the ability to draw broad conclusions. Additionally, several studies did not report the numerical data for material properties despite measuring them. Relatively few articles measured both material properties and running performance and assessed correlations.ConclusionSeveral articles connected prosthesis properties to running performance. However, inconsistent measurement and reporting of mechanical properties, along with the multifactorial nature of the athlete-prosthesis system, limit the ability to draw broad conclusions regarding the relationship between material and structural properties and athlete performance. Current evidence may be useful for clinicians seeking ways to optimize RSP stiffness in a case-by-case basis; however, clinicians would benefit from more consistent and systematic comparisons of the attributes of different RSPs and their role in performance.